Nokia Network Security Solutions Handbook - Maxwell, Doug (Syngress Publishing, 2011)
The Nokia Network Security Solutions Handbook introduces readers to both the basics and the finer points of administering, configuring, and securing the Nokia IP-series hardware appliances. It introduces readers to the different hardware models and covers the features associated with each. Installation and setup are covered in detail, as well as installation and configuration of the Check Point firewall on the Nokia system.